Probing the ATIC peak in the cosmic-ray electron spectrum with H.E.S.S. - Aharonian, F.; Akhperjanian, A.; Anton, G.; Barres de Almeida, U.; Bazer-Bachi, A.; Becherini, Y.; Behera, B.; Bernlöhr, K.; Bochow, A.; Boisson, C.; Bolmont, J.; Borrel, V.; et al. (EDP Sciences, 2009)
The measurement of an excess in the cosmic-ray electron spectrum between 300 and 800 GeV by the ATIC experiment has - together with the PAMELA detection of a rise in the positron fraction up to ˜100 GeV - motivated many interpretations in terms of dark matter scenarios; alternative explanations assume a nearby electron source like a pulsar or supernova remnant. Here we present a measurement of the cosmic-ray electron spectrum with H.E.S.S. starting at 340 GeV. While the overall electron flux measured by H.E.S.S. is consistent with the ATIC data within statistical and systematic errors, the H.E.S.S. data exclude a pronounced peak in the electron spectrum as suggested for interpretation by ATIC. The H.E.S.S. data follow a power-law spectrum with spectral index of 3.0±0.1(stat.)± 0.3(syst.), which steepens at about 1 TeV.